The Use Of Customary Law To Protect The Cultural Practices Of Indigenous Peoples In Hawai’i - Hare, C. Michael (Journal of Malaysian and Comparative Law, 2019)
The origin of contemporary judicial understanding in the United States of the law of custom is generally traced to Sir William Blackstone's Commentaries on the Law of England (1765). Several state courts, most notable Oregon and Hawai'i in recent years have used the doctrine to define public access to beaches and native gathering rights, respectively. To date, the United States Supreme Court has declined to review whether state court decisions using the doctrine of custom fail to comport with the takings requirements of the Fifth and Fourteenth Amendments to the constitution of the United States. This article reviews the case law treatment of issues posed by judicial use or litigants invocation of principles of customary law as potential model to apply to protect the cultural practices of indigenous peoples.